Kitchen and food production - Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
Demonstrate and illustrate the knowledge, skills, attitudes and behaviours need in running a large kitchen in hospitality industry. Also looks at the production of food in a major Australian airline.
Keywords: Food service management; Hospitality industry; Kitchens